Distribution and Sources of Aliphatic Hydrocarbons in Sediments from Sadong River, Sarawak, Malaysia - Omorinoye, Omolayo Ajoke; Zaini, Assim; Ismail, Jusoh; Durumin Iya, Naseer Inuwa; Sijuade Bamigboye, Olufemi; Aquisman Asare, Ebenezer (International Congress of Chemistry and Environment, 2020)
Twenty-one surface sediment samples collected from Sadong River, Sarawak were analysed for aliphatic hydrocarbons. These hydrocarbons were recovered from sediment by Soxhlet extraction and then analysed using gas chromatography equipped with mass spectrometer (GC-MS).